Implementasi Peran Dinas Lingkungan Hidup dalam Pengelolaan Sampah Rumah Tangga Di Kabupaten Sukoharjo - Andira Virna Ayundita; Rosita Candrakirana; Elizabeth Ayu Puspita Adi (Indonesian Journal of Social Sciences and Humanities, 2026)
This study aims to analyze the implementation of household waste management policies in Sukoharjo Regency based on Sukoharjo Regent Regulation Number 57 of 2018 concerning Regional Policies and Strategies in Household Waste and Household-like Waste Management. This legal research is a type of empirical legal research that is descriptive and analytical in nature, using data collection techniques such as interviews, field observations, and documentation. The results of this study show that the Sukoharjo Regency Environment Agency has made efforts to implement sustainable household waste management. The Environment Agency has implemented various programs in an effort to reduce and manage household waste. However, it cannot be denied that there are obstacles in the implementation of this policy program that have resulted in suboptimal household waste management. Its implementation is still hampered by uneven community participation and limited infrastructure. To address these obstacles, the Sukoharjo Regency Government has made efforts to formulate policies and strategies for household waste management in the form of policies to improve the performance of reducing household waste and similar waste, as well as policies to improve the performance of handling household waste and similar waste.